2006
DOI: 10.1177/0894318406289490
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of a Spiritually-Based Intervention and Self-Management in the Workplace

Abstract: This qualitative study assesses the experience of an intervention that provided spiritually based self-management tools to hospital-based nurses. Drawing on wisdom traditions of the major world religions, the eight point program can be practiced by adherents to any religious faith, or those outside of all traditions. Five of eight program points were perceived as directly useful in improving the nurses' workplace interactions and enhancing fulfillment of compassionate caregiving missions. The findings suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 10 publications
4
58
0
2
Order By: Relevance
“…Future research efforts must also be directed toward women and recent cohorts of returning Veterans from Iraq or Afghanistan to synthesize research with all eras of Veterans for patterns of similar reactions. Nevertheless, similar mantram stories describing the effect of calming and letting go of negative feelings have been found in other studies conducted in Veterans without PTSD [18], in adults living with human immunodeficiency virus [19], in family caregivers of Veterans with dementia [34], and in healthcare workers [35][36].…”
Section: Discussionsupporting
confidence: 73%
“…Future research efforts must also be directed toward women and recent cohorts of returning Veterans from Iraq or Afghanistan to synthesize research with all eras of Veterans for patterns of similar reactions. Nevertheless, similar mantram stories describing the effect of calming and letting go of negative feelings have been found in other studies conducted in Veterans without PTSD [18], in adults living with human immunodeficiency virus [19], in family caregivers of Veterans with dementia [34], and in healthcare workers [35][36].…”
Section: Discussionsupporting
confidence: 73%
“…Reports elsewhere document that EPP training produced trends towards reduced burnout (less emotional exhaustion, p 1 50.05, and more sense of personal accomplishment, p 1 50.10, on the Maslach Burnout Inventory), as well as some increases in vitality and job satisfaction ( p 1 50.10) . Similar findings are revealed by qualitative interviews (Richards et al, 2006). More broadly, the EPP may in part be viewed as a programme for self-care, a primary recommendation for preventing and alleviating compassion fatigue.…”
Section: Implications For Practicesupporting
confidence: 58%
“…Statistically significant treatment benefits were also reported for selected mental health indicators. Qualitative interviews with professional nurses (N ¼ 12) revealed several participants who reported increased abilities to experience compassion and empathy (Richards, Oman, Hedberg, Thoresen, & Bowden, 2006). Gains of about one-half SD, mediated by adherence to programme practices, were also reported in a 34-item measure of caregiving self-efficacy (perceived confidence, Oman, Richards et al, 2008).…”
Section: The Eight-point Programme Of Passage Meditationmentioning
confidence: 97%
See 1 more Smart Citation
“…Six of the 16 studies 19 19 found stress reduction to be a mediating factor in caregiving self-efficacy following a mindfulness intervention. 20 The second most widely measured concept was burnout. Burnout is described as the point in time when operation ceases or when a person can no longer function effectively.…”
Section: Methodsmentioning
confidence: 99%